A moderated-mediation analysis of performance appraisal politics perception and counterproductive work behavior - Wang, Hong-Yan; Chen, Zhi-Xia (Frontiers in Psychology, 2022)
Politics has become a common element in the performance appraisal process, and as decision recipients in this process, those appraised tend to be more sensitive to performance appraisal politics. This paper examines the mechanisms by which performance appraisal politics perception (PAPP) affects counterproductive work behavior (CWB) from the perspective of those appraised. The mediating effect of perceived organizational justice (POJ) and the moderating effect of political skill (PS) are incorporated into a parsimonious moderated-mediation model. A quantitative research approach is employed with survey data from 460 employees of large and medium-sized enterprises in Hubei Province (China), and structural equation modeling (SEM) and bootstrap analysis are used to test the proposed hypothesized relationships. The findings demonstrate that PAPP has a positive impact on CWB, and POJ partly mediates the relationship between PAPP and CWB. The results also reveal that individual PS moderates the positive correlation between PAPP and CWB. The academic and practical implications of these findings, as well as limitations and suggestions for future research, are also discussed.